Comparison between measurement of sodium and potassium by Blood Gas Analyzer versus Laboratory based Auto-analyzer among critically ill patients in a tertiary care hospital (Bangladesh Critical Care Journal, 2023)
Background: Electrolytes imbalances can lead to critical life threatening events so immediate and accurate assessmentis needed. There is always a time delay in receiving results from the central laboratory auto analyzer (AA). To overcomethis drawback, arterial blood gas (ABG) analyzer can be used as an alternative to measure electrolytes where resultscan be obtained within two minutes, allowing for prompt management.Methods: This cross-sectional study was carried out on 384 intensive care unit (ICU) patients of Bangladesh Instituteof Research and Rehabilitation in Diabetes, Endocrine and Metabolic disorders (BIRDEM) General Hospital. Theaverage values of sodium and potassium in ABG analyzer and laboratory AA were calculated and then the meandifference or bias was obtained of sodium and potassium measurements analyzed by the two methods. Bland-Altmanplot and Lin’s concordance correlation coefficient (ρc) was used to measure the agreement between the two methods.Test results were considered reliable, if the bias was non-significant and within the United States Clinical LaboratoryImprovement Amendment (US CLIA) criteria (±4 mmol/l for sodium and ±0.5 mmol/l for potassium), 95% limits ofagreement (LOA) were narrow and ρc showed good concordance.Results: The mean difference or bias, 95% LOA and ρc for sodium was -1.2 mmol/l, -11 mmol/l to 8.6 mmol/l and 0.85respectively whereas for potassium this was 0.8 mmol/l, -0.39 to 1.98 mmol/l and 0.63 respectively. The bias for sodiumwas within the US CLIA criteria but not so for potassium. However, the 95% LOA was wide and there was poorconcordance for both the measurement. On account of these differences, correction factor was calculated for sodiumand potassium values. Serum sodium (in mmol/l) was 2.48 + 0.97 x ABG sodium (in mmol/l) and serum potassium (inmmol/l) was 1.18 + 0.89 x ABG potassium (in mmol/l).Conclusion: The sodium and potassium measurements obtained from the ABG analyzer was found to be unreliable.However, a correction factor to the ABG analyzer results could be applied to initiate treatment and then changing themanagement, if required, once laboratory AA reports become available.Bangladesh Crit Care J March 2023; 11 (1): 3-8